Nutrition Intake of Golden Period of Life - Sasube, Laurensi M.; Luntungan, Aldian H. (Jurnal Ilmu dan Teknologi Pangan, 2017)
Quality human resources are determined from the fulfillment of child nutrition from an early age even while still in the womb known as the first 1000 days of life (1000 HPK). This period starts from the pregnancy phase (270 days) until the child is 2 years old (730 days). The first thousand days of life have been agreed as the most important period in life because it can determine the health and intelligence of human resources in the future. The first thousand days of life represent a period of growth and development in all organs and systems of the body. Nutritional problems related to maternal nutritional status during pregnancy and lactation will affect the health of newborns, 2-year-olds and young women in the future Unmet needs in this period will have a permanent effect. The impact is not only on physical growth, but also on the mental development, intelligence, and behavior of children. Maternal nutrition during pregnancy has an effect on maternal mortality and infant mortality that is an indicator of a country's health progress.Keywords: golden period, nutrition intake, nutrition status